KAJIAN BIOMEKANIK TEKNIK PENDARATAN PAYUNG TERJUN BAGI TENTERA MALAYSIA DENGAN KAEDAH KANE DAN ANALISIS DATA FUNGSIAN - Noor Syazwana Abd Aziz (Tesis, 2022)
The aim of this research to develop a whole-body mathematical model of parachute landing activities to identify the best landing techniques and reduce the risk of injury.